Theory and practice of participation on BBC’s Question Time - Ferreira Seridório, Daniele; Rothberg, Danilo (Brazilian journalism research, 2022)
ABSTRACT – Connections between public service broadcasters and viewers can take place in a variety of contexts, including TV programs where practices of interaction and participation seek to ensure the fulfillment of public media duties. Our research developed an analysis of BBC’s Question Time, a television show first broadcast in 1979 and still on. Our goal was to investigate theoretical and empirical aspects of audience participation in the program. Our methods were document and program analysis, and interviews with BBC journalists. The results include a wide view of how Question Time and the participation it provides have evolved. We argue that participation in the media may be a way of reinforcing public service broadcasting commitments with the health of democracy. RESUMO – As conexões entre emissoras de serviço público e telespectadores podem ocorrer em uma variedade de contextos, incluindo programas de TV onde as práticas de interação e participação procuram assegurar o cumprimento das obrigações da mídia pública. Nossa pesquisa desenvolveu uma análise do Question Time da BBC, programa transmitido pela primeira vez em 1979 e ainda em andamento. Nosso objetivo foi investigar aspectos teóricos e empíricos da participação do público no programa. Nossos métodos foram a análise de documentos e programas, e entrevistas com jornalistas da BBC. Os resultados incluem uma visão ampla sobre como o Question Time e a participação proporcionada através do programa evoluíram ao longo do tempo. Argumentamos que a participação na mídia pode ser uma forma de reforçar os compromissos do serviço público de radiodifusão com a saúde da democracia. RESUMEN – Las conexiones entre los servicios públicos de radiodifusión y los telespectadores pueden producirse en diversos contextos, incluidos los programas de televisión, donde las prácticas de interacción y participación buscan asegurar el cumplimiento de las obligaciones de los medios de comunicación pública. Nuestra investigación analizó el programa Question Time de la BBC, emitido por primera vez en 1979 y aún vigente en la actualidad. En particular, se abordaron los aspectos teóricos y empíricos de la participación del público en el programa. La metodología abarcó tanto el análisis de documentos y programas, como la realización de entrevistas con periodistas de la BBC. Los resultados proporcionan una visión amplia sobre cómo ha evolucionado Question Time y sus formas de participación, a lo largo del tiempo. Sostenemos que la participación en los medios de comunicación puede ser una manera de reforzar los compromisos de los servicios públicos de radiodifusión con la salud de la democracia.